Предмет: Алгебра,
автор: lolkhusainov
выполните умножение
(a-4)(a-2)
(3x+1)(5x-6)
(3y-2c)(y+6c)
(b+3)(b²+2b-2)
Ответы
Автор ответа:
2
Ответ:
Должно быть правильно)
Объяснение:
Приложения:
![](https://files.topotvet.com/i/f91/f9140534709983f9645570fcecc54145.jpg)
Автор ответа:
0
Ответ:
Объяснение:
1. (а-4)(а-2)= а²-2а-4а+8=а²-6а+8= дальше квадратное уравнение через дискриминант
2. (3х+1)(5х-6)= 15х²-18х+5х-6=15х²-13х-6
3. (3у-2с)(у+6с)= 3у²+18ус-2ус-12с²=3у²+16ус-12с²
Похожие вопросы
Предмет: Математика,
автор: ogastovtopchik98
Предмет: Математика,
автор: siruginam
Предмет: Математика,
автор: animag3456
Предмет: Математика,
автор: камила20053
Предмет: Математика,
автор: денсуханкин